Estimation of Carbon Stock as an Impact of Land Use Change in Anduonohu Village, Poasia District, Kendari City - Syafrul Tawakal, Achmad; Gandri, La; Indriyani, Lies; Saleh Qadri, Muhammad; Rahmatiah Tuwu, Eka (University of Jember, 2025)
The rapid development of Kendari City has led to numerous changes in land use for commercial activities, thereby unknowingly reducing stored carbon reserves. The change in forest function, which is dominated by land for human settlement and trade activities, has reduced the amount of stored carbon reserves. Anduonohu Village is the largest village in the Poasia District, covering an area of 14.11 km²(32.88% of the total area of the Poasia District). The rapid development of Kendari City has led to numerous land changes for commercial activities, thereby reducing stored carbon reserves. The objectives of this study are 1) to determine land use in Anduonohu Village, Poasia District, Kendari City, and 2) to determine carbon reserves as a result of land use changes in Anduonohu Village, Poasia District, Kendari City. This research was conducted in Anduonohu Village in June-July 2023. The research method used was a quantitative descriptive method with data collection techniques, namely observation, documentation, and literature study techniques, and using spatial analysis to analyze the quantitative data obtained. The results obtained in this study are 1) land use in Anduonohu Village in 2018 and 2022 is divided into seven types, namely secondary dryland forest, plantations, secondary mangrove forest, settlements, shrubs/scrub, additional land, and open land. Of the seven types of land use in Anduonohu Village, the largest land change between 2018 and 2022 was in the residential area, which increased by 487 ha. 2) The amount of carbon reserves in Anduonohu Village in 2018 was 868.354 tons/ha and decreased to 822.181 tons/ha in 2022 from the seven types of land use in Anduonohu Village.ha in 2022 from the seven types of land use in Anduonohu Village.